PRODUCT PLACEMENTEXECUTION FACTOR AND INDIVIDUAL DIFFERENCES EFFECT ON PURCHASE INTENTION THROUGH CONSUMER’S ATTITUDE IN INDONESIA - Aleksandra Sekar Melati; Edi Abdurachman (Bina Nusantara University, 2018)
Comic books industry in Indonesia is a growing business, yet the creators and the publishers rarely publish local books due to consumers looking at comic books as a low-priced entertainment while being expensive to make. Product placement in comic books is a way to rise funding forpublishers with low profit margin and a way for brands to advertise their company’s products. This research objective is to identify the significant factors in brand attitude regarding the product placement in comic book and therefore the purchase intention of said brand. The research is done through a survey. The questionnaires distributed among the members of Indonesia Comic community i.e.Komunitas Mangaka using simple random sampling technique. Data analysis method used to process the data was multiplelinear regression. From the proposed seven hypotheses, five are supported. Individual factors turned out to be significant in influencing people’s attitude and therefore the purchase intention. Product placement is also significantly increasing brand interest and opinion according to this study. Personal Attitude towards product placement in general is confirmed to be the most significant factor in influencing the attitude towards the brand placed in comic book while the way it’s executed doesn’t significantly affect one’s attitude and purchase intention. Product placement is therefore recommended for companies to consider product placement as advertising strategy.